A comparison of two bidirectional air-surface exchange models for gaseous elemental mercury over vegetated surfaces. (1st February 2021) - Hao, Jingliang; Xu, Xiaohong; Lin, Che-Jen; Zhang, Leiming
Abstract: Uncertainties exist in the current estimates of atmospheric dry deposition and air-surface exchange of atmospheric mercury in chemical transport models and monitoring networks. To quantitatively assess these uncertainties, two bidirectional air-surface exchange models for gaseous elemental mercury (Hg 0 ), originally developed by Wang et al. (2014, Atmos. Chem. Phys., doi:10.5194/acp-14-6273-2014) and Wright and Zhang (2015, J. Adv. Model. Earth Syst., doi:10.1002/2014MS000367), were compared quantitatively. The two models were applied to two vegetated land covers, including a deciduous broadleaf forest and a cropland, near a monitoring site in Georgia, USA for calculating air-surface exchange fluxes of Hg 0 . The model inputs include measured 2-hourly ambient Hg 0 concentrations and archived surface meteorology data produced from a weather forecast model. The estimated annual net fluxes differed significantly between the two models, i.e., −0.7 μg m −2 yr −1 by Wang et al.'s model vs. −8.6 μg m −2 yr −1 by Wright & Zhang's model over the deciduous broadleaf forest and 8.4 μg m −2 yr −1 vs. −10.7 μg m −2 yr −1 over the cropland. When considering dry deposition and emission fluxes separately, similar deposition fluxes were produced by the two models, regardless of season and land cover, due to the similar canopy resistance formulas used in the two models. Much higher soil and lower stomatal emission fluxes were produced by Wang et al.'s model than Wright & Zhang's model (soil: 30 vs. 8.9 μg m −2 yr −1 and stomata: 0.5 vs. 8.3 μg m −2 yr −1, averaged over the two canopies) due to the very different emission potentials used in the two models. Cuticle emission fluxes contributed less than 0.1% to the total emission flux in Wang et al.'s model, and were not considered in Wright & Zhang's model. The differences in soil emission flux, total emission flux, and net flux were more pronounced in winter than in the other seasons. The large differences in the net fluxes between the two models were primarily caused by their very different schemes of soil emission potential. Highlights: Compared two bidirectional air-surface exchange models of gaseous elemental mercury. Annual & seasonal net exchange fluxes differed significantly between the two models. Separating deposition & emission fluxes allows analyzing reasons of differed fluxes. Large differences in emissions due to different schemes of soil emission potential. Different stomatal emission potentials also led to discrepancies in emissions.